Working Productively with Indigenous Communities: Mungullah Best Start Playgroup - Lee, Libby; Thompson, Andrew (The Australian Journal of Indigenous Education, 2007)
Abstract In this paper, we discuss and analyse the development of a resource documenting an Indigenous early childhood playgroup programme. The resource, known as the “Best Start DVD” was developed through a partnership between community and government support agencies to support engagement of parents as educators of their children. Through analysis of the development process and the product, we provide commentary on our learning regarding working successfully in partnerships with Indigenous communities. Additionally, we discuss what we learned about influences on Indigenous parents’ engagement as educators of their children.